TRANSFORMASI CERITA KOLONIAL DALAM TEKS “ORANG RANTAI” - Yosi Wulandari; Wachid Eko Yosi; Fitri Merawati (tuahtalino, 2019)
The purpose of this study is to describe (1) the authors' reception of the colonial discourse in the text of "Orang Rantai"; (2) forms of transformation of the colonial story in the text of "Orang Rantai". This research is descriptive qualitative research type with content analysis method. The approach of this research is the literature of intertextuality appeals with the application of literary receptions theory. The theory of literary reception used is Hans Robert Jauss, Jaus states that the aesthetics of the reception itself is essentially a synthesis of poetic theory and also the theory of interpretation or often called hermeneutics. The object of this research is the story of "Orang Rantai”. The subject of this research is the story of the people "Orang Rantai" is a story that originated from the area Sawahlunto West Sumatra which began as an oral literature, the book “Orang Rantai” written by TIM Lecturer Department of Language and Literature Indonesia UNP, and short story "Orang Rantai" by Pinto Anugrah. Data were collected by interview, transliteration, data inventory, literature study, analysis and interpretation, and conclusions. The result of this study is the transformation of colonial discourse in the text of the chain of content is maintained but there is a change of shapes and styles of storytelling based on the author's receptions of the text of the preceding chain. Transformation of the text is a manifestation as the writer can not avoid the influence of the preceding text and the story is the present according to the times..